Penguatan Literasi Digital Dalam Pemanfaatan Website Pada Badan Usaha Milik Desa Cibogo - Indah Umiyati; Trisandi Eka Putri; Icih Icih; Bambang Sugiharto; Daeng M. Nazier (Pakis Journal Institute, 2024)
This community service activity aims to improve digital literacy in website utilisation at BUMDes in Subang Regency, namely BUMDes Cibogo. The scope of digital literacy in this activity is Digital Skill, which is the ability of individuals to know, understand, and use ICT hardware and software as well as digital operating systems in everyday life. The methodology used in this activity is Rapid Rural Appraisal (RRA), a strong approach to rural community development. RRA includes aspects of respecting the community, encouraging the community to express and share ideas or opinions, asking questions, listening attentively, and taking notes. After the community service activities, the management of BUMDes Cibogo understands digital literacy at the digital skill level and a perception that digital literacy is very important as an effort to optimise BUMDes performance.